(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The book and Netflix series Selection Day by Aravind Adiga tells a gripping story of two brothers in Mumbai, their controlling father, and the demands of playing cricket to escape poverty. Rich descriptions and a more complex comprehension of the characters’ motivations and problems are provided by the novel’s deep dive into the characters’ inner thoughts and feelings. The plot can be developed gradually because to the book’s pacing, which gives readers time to comprehend the intricacies of the people and their surroundings. Adiga’s unique language style is defined by his astute observations of Indian society and his incisive social commentary. The book deftly and intricately examines a number of topics, including ambition, familial pressure, and the socioeconomic difficulties facing contemporary India. With vivid depictions of Mumbai and the cricket scene, the series graphically brings the story to life and opens it up to a wider audience. In order to achieve dramatic effect, the series omit or change certain events, which result in a faster-paced story than in the novel. This paper analyzes about the novel to Netflix series and the transformation on screen. To fit the medium or appeal to a wide range of viewers, certain plot points, characters, or themes are changed or emphasized in the series in different ways.